The structural rearrangement of testicular arteries in case of chronic ethanol intoxication - S.O. Nesteruk; M.S. Hnatiuk; L.Ya. Fedoniuk; I.I. Smachylo; I.Ya. Krynytska; M.I. Marushchak (Group of Companies Med Expert, LLC, Kyev, Ukraine, 2023)
Prolonged poisoning of the body with ethanol damages almost all its organs and systems. Structural changes in testicular arteries under the influence of chronic ethanol intoxication have not been fully studied. Purpose - to analyze the morphometric parameters of the small caliber arteries of the right and left testicles of rats in case of chronic ethanol intoxication. Materials and methods. 62 laboratory sexually mature male rats was performed. The animals were divided into two groups. The Group 1 (control) included 30 rats, the Group 2 (experimental) - 32 animals. The experimental rats, which were conducted to the experiment, were injected intragastrically with a 30% ethanol solution at the rate of 2 ml per 100 g of body weight for 28 days once a day. Animals were euthanized by heart bleeding under thiopental anesthesia. Histological micro-sections were made from the left and right testicles. Morphometrically, the outer and inner diameters of the arteries, media thickness, adventitia, Vogenvoort and Kernogan indices, the height of endotheliocytes, the diameter of their nuclei, the nuclear-cytoplasmic ratio in these cells, and the relative volume of damaged endotheliocytes were determined morphometrically in small-caliber arteries. Statistical processing of digital data was carried out using Excel (Microsoft, USA) and STATISTICA 6.0 (Statsoft, USA) software. Results. It was established that in case of simulated experimental conditions of chronic ethanol intoxication, the investigated morphometric parameters of the arteries of the left and right testicles changed significantly. In case of chronic intoxication with ethanol in rats, pronounced structural rearrangement of testicular vessels, mainly small arteries, characterized by thickening of the blood vessel's wall, narrowing of vessels' lumen, rearrangement of endothelial cells, and an increase in the relative volume of the damaged cells of intima, is established, and is dominant in the left testis. Conclusions. In case of chronic intoxication with ethanol the structural changes in testicular tissues are dominant in the left testis. Pronounced remodeling of small caliber testicular arteries causes endothelial dysfunction, deterioration of blood supply to the testicles, hypoxia, dystrophic and necrobiotic tissue changes, infiltrative and sclerotic processes, which are the pathomorphological basis of male infertility. When carrying out experiments with laboratory animals, all bioethical norms and recommendations were observed. No conflict of interests was declared by the authors.